1996
DOI: 10.1007/bf00169180
|View full text |Cite
|
Sign up to set email alerts
|

Contraction and relaxation of aortas from diabetic rats: effects of chronic anti-oxidant and aminoguanidine treatments

Abstract: We examined whether chronic treatment with the free radical scavengers butylated hydroxytoluene (1 g kg-1 day-1) and N-acetyl-L-cysteine (250 mg kg-1 day-1), or the inhibitor of advanced glycosylation reactions, aminoguanidine (1 g kg-1 day-1), could prevent the development of relaxation and contraction abnormalities in aorta from 2 month streptozotocin-diabetic rats. Diabetes caused a 24% deficit in maximal endothelium-dependent relaxation to acetylcholine for phenylephrine precontracted aortas (P < 0.01). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 36 publications
(46 reference statements)
3
38
0
Order By: Relevance
“…This contrasts with previous studies that demonstrated that aminoguanidine treatment of diabetic rats improved vasodilation in the aorta [46,47]. In addition, Cartledge et al [64] have demonstrated that the formation of advanced glycation endproducts is probably responsible for the impairment of endothelialdependent penile smooth muscle relaxation seen in diabetes.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…This contrasts with previous studies that demonstrated that aminoguanidine treatment of diabetic rats improved vasodilation in the aorta [46,47]. In addition, Cartledge et al [64] have demonstrated that the formation of advanced glycation endproducts is probably responsible for the impairment of endothelialdependent penile smooth muscle relaxation seen in diabetes.…”
Section: Discussionmentioning
confidence: 65%
“…These studies suggest that vascular dysfunction is an important factor underlying nerve conduction deficits and reduced endoneurial blood flow early in the development of diabetic neuropathy. This is supported by earlier studies that demonstrated diabetesinduced impairment in vasoreactivity in the sciatic nerve is due to reduced nitric oxide mediated endothelium-dependent relaxation [37,38].In spite of the large number of studies regarding the efficacy of treatment of diabetic [46,47]. This could be due to a decrease in advanced glycation end products, which have been demonstrated to quench nitric oxide activity [48].…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…Where measured, there was accompanying improvement in nerve perfusion and prevention of defective NOmediated endothelium dependent relaxation. Indeed, such effect was seen by treatment with butylated hydroxytoluene, a lipophilic scavenger (Archibald et al, 1996) and antioxidant effects to improve nerve blood flow and NCV in diabetic rats are blocked by cotreatment with a low dose of a NO synthase inhibitor .…”
Section: Introductionmentioning
confidence: 99%